Propensity to Use Additional Forms of Retirement Security in The Context of the Current Retirement Age in Poland - Wanda SULKOWSKA (Communications of International Proceedings, 2021)
Motivation: Due to demographic changes, in 2013 a gradual increase in the retirement age was introduced in Poland, ultimately to 67 for both sexes.  However, in 2017, the previous retirement age was restored. In this situation, it is necessary for professionally active people to use other voluntary programs for financial security during the retirement period, offered under the third pillar of retirement insurance. The uptake of these programs before 2013 was far from sufficient. Has the change in the retirement age in 2017 influenced this state of affairs? Aim: The aim of the research carried out on a group of the Lesser Poland residents was to obtain information on the inclination of Poles to take advantage of savings programs in the third pillar in the context of their assessment of the applicable retirement age, taking into account the age, gender, education and place of residence of the respondents. Results: Despite the few years that have passed since the lowering of the retirement age in Poland, the general awareness of the risks associated with it is still low, and thus the propensity to voluntarily accumulate funds earlier in the retirement period is too low. There are significant differences in this regard. The above problem concerns mainly supporters of keeping the retirement age in Poland at a low level and is characteristic of people with low or secondary education, people who have already left the labour market or are just starting their professional activity, inhabitants of rural areas and smaller towns.
Keywords: Propensity to Save; Retirement Age; Use of Additional Forms of Saving for Retirement.